FACTORS ASSOCIATED WITH FEAR OF FALLING IN PATIENTS WITH KNEE AND HIP OSTEOARTHRITIS (Tạp chí Y học Cộng đồng, 2026)
Objective: To identify factors associated with fear of falling among patients with knee and/or hip osteoarthritis.Subjects and Methods: A descriptive cross-sectional study was conducted on 151 patients aged ≥40 years with knee and/or hip osteoarthritis who were examined and treated at University Medical Center Ho Chi Minh City from January 2025 to April 2025. Patients were diagnosed according to the ACR 1991 criteria. Fear of falling was assessed using the Falls Efficacy Scale–International (FES-I).Results: The study included 151 patients with knee and/or hip osteoarthritis. A history of falls (OR = 3.88, p = 0.006) and the WOMAC physical function score (OR = 1.11, p = 0.045) were independently associated with a high level of fear of falling.Conclusion: A history of falls and impaired physical function, particularly lower limb functional limitations, were independently associated with a high level of fear of falling. Assessment and interventions aimed at improving physical function should be emphasized to help reduce fear of falling and prevent falls in the community.
Keywords: Fear of falling, falls, osteoarthritis